2016
DOI: 10.1016/j.bbrep.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A novel SOD mimic with a redox-modulating mn (II) complex, ML1 attenuates high glucose-induced abnormalities in intracellular Ca 2+ transients and prevents cardiac cell death through restoration of mitochondrial function

Abstract: A key contributor to the pathophysiology of diabetic cardiomyopathy, mitochondrial superoxide can be adequately countered by Mn-superoxide dismutase, which constitutes the first line of defense against mitochondrial oxidative stress. Our group has recently synthesized low molecular weight SOD mimics, demonstrating superior protection against oxidative damages to kidney cells. In the current study, we sought to evaluate the protective effect of the SOD mimic ML1 against high glucose induced cardiomyopathy in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…At the same time, MCU and MICU1 are major highly selective channels for m Ca 2+ uptake, and the transportation of Ca 2+ depends on the electrochemical gradient of MMP [ 38 ]. In a high glucose environment, the MMP of 3T3-L1 adipocytes decreases, forming a vicious cycle [ 39 ]. Previous studies have shown that m Ca 2+ effects membrane potential and ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, MCU and MICU1 are major highly selective channels for m Ca 2+ uptake, and the transportation of Ca 2+ depends on the electrochemical gradient of MMP [ 38 ]. In a high glucose environment, the MMP of 3T3-L1 adipocytes decreases, forming a vicious cycle [ 39 ]. Previous studies have shown that m Ca 2+ effects membrane potential and ATP production.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that after the application of MCU inhibitors, mitochondrial calcium homeostasis has been disturbed and further led to mitochondrial oxidative respiratory dysfunction and membrane potential loss [26] . Mitochondrial Ca 2+ uptake depends on the mitochondrial membrane potential, and the myocardial cell mitochondrial membrane potential decreases in a high-glucose environment, thus forming a vicious cycle, which ultimately leads to cell apoptosis [27] . The present experimental results showed that the calcium homeostasis high glucose group H9C2 cardiomyocytes had reduced ATP production, decreased membrane potential, and increased apoptosis.…”
Section: Discussionmentioning
confidence: 99%